Proteomics-inspired precision medicine for treating and understanding multiple myeloma. Issue 2 (3rd March 2020) - Ho, Matthew; Bianchi, Giada; Anderson, Kenneth C.
ABSTRACT: Introduction : Remarkable progress in molecular characterization methods has led to significant improvements in how we manage multiple myeloma (MM). The introduction of novel therapies has led to significant improvements in overall survival over the past 10 years. However, MM remains incurable and treatment choice is largely based on outdated risk-adaptive strategies that do not factor in improved treatment outcomes in the context of modern therapies. Areas covered : This review discusses current risk-adaptive strategies in MM and the clinical application of proteomics in the monitoring of treatment response, disease progression, and minimal residual disease (MRD). We also discuss promising biomarkers of disease progression, treatment response, and chemoresistance. Finally, we will discuss an immunomics-based approach to monoclonal antibody (mAb), vaccine, and CAR-T cell development. Expert opinion : It is an exciting era in oncology with basic scientific knowledge translating in novel therapeutic approaches to improve patient outcomes. With the advent of effective immunotherapies and targeted therapies, it has become crucial to identify biomarkers to aid in the stratification of patients based on anticipated sensitivity to chemotherapy. As a paradigm of diseases highly dependent on protein homeostasis, multiple myeloma provides the perfect opportunity to investigate the use of proteomics to aid in precision medicine.